INTEGRATION OF NAQLI AND AQLI IN THE STUDY OF THE QURAN AND SUNNAH: A DESCRIPTIVE ANALYSIS - Md Yousuf Ali; Md Bahar Uddin; Md Redowanul Karim (International Prophetic Conference (SWAN) FPQS USIM, 2024)
The integration of Naqli (revealed knowledge) and Aqli (rational knowledge) in the study of the Qur’an and Sunnah has become a new tendency in the contemporary academia history of the Muslims’ academic institutions. The integrated approach is essential to harmonize revealed knowledge with rational knowledge. Instances of integrated curriculum can be found in modern context in some universities and academic institutions such as IIUM, IIIT, USIM in Malaysia, and International Islamic university Islamabad Pakistan. Naqli knowledge is the divine revelation or absolute knowledge such as the Qur'an and Hadith, while Aqli is the rational, intellectual, and empirical knowledge. In the context of Qur’an and Sunnah studies, integrating these two forms of knowledge involves harmonizing traditional Islamic scholarship with contemporary scientific and philosophical knowledge. The paper therefore examines the concept, brief history, and methods of the integration of naqli and aqli in the study of the Qur`an and Sunnah, and analyses these within the purview of Islamic thought, which is based on the argumentations of the Qur`anic and Hadith studies. The paper concludes with a suggestion on the need to revisit the issues of the significance of the traditional Islamic scholarship in bridging modern scientific and philosophical knowledge in our times, particularly in the light of the modern integration of knowledge process. The study concludes that integrated approach can offer comprehensive solutions of the contemporary challenges in the study of the Quran and Sunnah for the wellbeing of modern man and society.